1976
DOI: 10.1111/j.1399-0004.1976.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial pericentric inversion of chromosome 19, inv(19) (p13q13) with a note on genetic counseling of pericentric inversion carriers

Abstract: An inmate of a hospital for the mentally retarded was found during a cytogenetic screening programme to have karyotype 46,XY,inv(19)(p13q13)mat. Clinical, cytogenetic and family findings are presented and it is concluded that the chromosome abnormality was probably not the cause of the patient's retardation. The problem of genetic counselling of inversion carriers is examined in some detail and estimates of risk are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 18 publications
2
14
0
3
Order By: Relevance
“…However, in some families the female carriers appear to be at higher risk of producing unbalanced offspring than the male carriers are (Sutherland et al 1976;Pai et al 1987). Studies performed by Kaiser (1988) confirm these results: paternal inversions were found to be causative in 36 cases of unbalanced offspring as compared to maternal inversions in 46 cases.…”
Section: Genetic Risks For Carriers Of Inversionssupporting
confidence: 71%
“…However, in some families the female carriers appear to be at higher risk of producing unbalanced offspring than the male carriers are (Sutherland et al 1976;Pai et al 1987). Studies performed by Kaiser (1988) confirm these results: paternal inversions were found to be causative in 36 cases of unbalanced offspring as compared to maternal inversions in 46 cases.…”
Section: Genetic Risks For Carriers Of Inversionssupporting
confidence: 71%
“…However, in families with a positive history for previous recombinants, there is a significant recurrence risk. This risk has been estimated to be 5 % for male and 10 % for female inversion carriers to produce a chromosomally abnormal child (Sutherland et al 1976, Vigi et al 1977. Of particular significance to this case is a review of pericentric inversions involving t h e p l l q l 2 region of chro- mosome 18 (Vigi et al 1977).…”
Section: Discussionmentioning
confidence: 91%
“…There is a great deal of variation in the estimates of the risks of recombinants occurring. Inversions involving a small portion of certain chromosomes, such as number 9, occur with a frequency of approximately 1 % (de la Chapelle et al 1974) and may be inherited without apparent risk for recombination (Sutherland et al 1976). However, in families with a positive history for previous recombinants, there is a significant recurrence risk.…”
Section: Discussionmentioning
confidence: 99%
“…Серед 600 осіб із вродженими вадами розвитку, затримкою розумового розвитку, ПП зі звичним НВ, мертвонародженням та народженням дітей із синдромом Дауна перицентрична інверсія зустрічалась у 4% випадків [39]. В нашому дослідженні загальна поши-реність перицентричної інверсії хромосоми 9 склала 1,7% (серед жінок -1,49%, серед чоловіків -2,07%).Частота перицентричної інверсії Y-хромосоми inv (Y) (p11q11) загалом складає 1-2 випадки на 1000 [40], але варіює в різних популяціях. Наприклад, при цитогенетич-ному дослідженні 14 835 новонароджених в японській по-пуляції було знайдено лише один випадок інверсії Y, тоді як серед мусульманського населення Південної Африки ця інверсія була знайдена в 5,7% [41], а серед тайванського -лише в 0,27% [28].…”
unclassified
“…Частота перицентричної інверсії Y-хромосоми inv (Y) (p11q11) загалом складає 1-2 випадки на 1000 [40], але варіює в різних популяціях. Наприклад, при цитогенетич-ному дослідженні 14 835 новонароджених в японській по-пуляції було знайдено лише один випадок інверсії Y, тоді як серед мусульманського населення Південної Африки ця інверсія була знайдена в 5,7% [41], а серед тайванського -лише в 0,27% [28].…”
unclassified